Human Resource Panning and its Impact on Organizational Performance in Ministry of Health, Abuja - Khalipha Abba Abdulkadir (International Studies Journal)
This study examines how Human Resources Planning (HRP) impacts Organisational Performance. It specifically determined how the impact of job analysis on Ministry of Health performance, the impact of staff demand and supply forecasting and employee retention planning on the Ministry's performance. The respondents' data was collected using descriptivemethodology research. The study's target population was 100 workers from the Ministry of Healthin Abuja, Nigeria. The sample size of thirty workers, or thirty percent of the target population, was chosen using stratified random selection methods. Questionnaires were utilized to gather information. The information gathered was evaluated using average weighted and percentages, which were then displayed in frequency charts and tables.According to the findings, the business uses job analysis questionnaires regularly. Job analysis at the workplace improves the company's competitive edge. Internal promotion is the most important element examined by the organisation in employee supply forecasting, whereas demand for products and services is the most important factor considered by the Ministry of Health in employee demand forecasting. Employee demand forecasting assists an organisation in addressing current and future people requirements. The main factor of a successful staff retention strategy in an organisation is an attractive pay package. The organisations's retention strategy is heavily influenced by support for personal and professional growth. It'ss competitive edge is boosted through retention strategy. The researcher concluded that staff retention planning, demand-supply forecasting, and job analysis all have an impact on the success of an organisation.